Laser drilling of microholes in single crystal silicon using continuous wave (CW) 1070 nm fiber lasers with millisecond pulse widths - Maclean, Jessica O.; Hodson, J.R.; Tangkijcharoenchai, C.; Al-Ojaili, S.; Rodsavas, S.; Coomber, S.; Voisey, K.T. (Old City Publishing, 2018)
The laser microdrilling of via holes in Si semiconductor wafers was studied using 1 ms pulses from an Yb fibre laser with 1070 nm wavelength. Optical microscopy and cross‑sectional analysis were used to quantify hole dimensions, the distribution of recast material and any microcracking for both (100) and (111) single crystal surface semiconductor wafer orientations. The flexibility of this laser wavelength and simple pulsing scheme were demonstrated for a range of semiconductor substrates of narrow and wide bandgap including InSb, GaSb, InAs, GaAs, InP and sapphire. Detailed observations for Si showed that, between the threshold energies for surface melting and the irradiance for drilling a “thru” hole from the front surface to rear surface, there was a range of irradiances for which microcracking occurred near the hole circumference. The directionality and lengths of these microcracks were studied for the (100) and (111) orientations and possible mechanisms for formation were discussed, including the Griffith criterion for microcracks and the failure mechanism of fatigue usually applied to welding of metals. Above the irradiance for formation of a thru hole, few cracks were observed. Future work will compare similar observations and measurements in other narrow- and wide-bandgap semiconductor wafer substrates.